New Species of Campodeidae (Diplura) from Mexican caves - Sendra, Alberto; Palacios, Jose; Garcia, Arturo; Montejo, Maira (Zootaxa, 2016)
Six new taxa of Campodeidae (Diplura) are described in the genera Litocampa, Juxtlacampa, Oncinocampa, and Tachycampa. We also redescribe the interesting species Juxtlacampa juxtlahucensis Wygodzinsky, 1944 from Juxtlahuaca cave in Guerrero, Mexico. All of these taxa are cave-dwelling species with more or less noticeable troglobiomorphic features They inhabit the subterranean ecosystem in six limestone massifs and one lava tube cave in the central states of Mexico. Four of these species are included in the “tachycampoide” group and one species in the “podocampoide” group (sensu Bareth & Conde). Nine species already known in Central and South America of the “tachycampoide” group, in such poorly-sampled regions compared with the eight species in the well-sampled Mediterranean region (Ibero-Sardinia and north Africa), suggest an American origin for this group.